2019
DOI: 10.3389/fphys.2019.01233
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Its Implications in the Right Ventricular Remodeling Secondary to Pulmonary Hypertension

Abstract: Pulmonary hypertension (PH) is a pulmonary vascular disease characterized by increased pulmonary artery pressures. Long standing pulmonary arterial pressure overload leads to right ventricular (RV) hypertrophy, RV failure, and death. RV failure is a major determinant of survival in PH. Oxidative stress has been associated with the development of RV failure secondary to PH. Here we summarize the structural and functional changes in the RV in response to sustained pulmonary arterial pressure overload. Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 75 publications
1
14
0
Order By: Relevance
“…The pathological mechanism of HPH is very complicated. Consistent with network analysis, previous studies have demonstrated that the development of pulmonary hypertension is highly related to oxidative stress ( Mikhael et al, 2019 ; Li et al, 2020 ; Türck et al, 2020 ). Our preliminary experiments show that DSY has no effect on PH induced by monocrotaline (results are not shown), but is effective for HPH.…”
Section: Discussionsupporting
confidence: 80%
“…The pathological mechanism of HPH is very complicated. Consistent with network analysis, previous studies have demonstrated that the development of pulmonary hypertension is highly related to oxidative stress ( Mikhael et al, 2019 ; Li et al, 2020 ; Türck et al, 2020 ). Our preliminary experiments show that DSY has no effect on PH induced by monocrotaline (results are not shown), but is effective for HPH.…”
Section: Discussionsupporting
confidence: 80%
“…Pulmonary hypertension (PH) is a vascular disease that is characterized by increased pressure in pulmonary arteries. It is well known that long standing pressure overload leads to right ventricular (RV) hypertrophy, RV failure, and even death [1,2]. Then treatments for PH mainly reduce pulmonary vascular resistance by promoting the balance between vasoconstriction and vasodilation.…”
Section: Introductionmentioning
confidence: 99%
“…However, when alveolar hypoxia is maintained, the hypoxic pulmonary vasoconstriction mechanism is exacerbated and can trigger vascular remodeling ( León-Velarde et al, 2010 ; Tan et al, 2017 ) and, subsequently, pulmonary hypertension, or HAPH ( Penaloza et al, 1964 ; Xu and Jing, 2009 ; León-Velarde et al, 2010 ). As mentioned above, pulmonary hypertension is a disease characterized by pulmonary vascular remodeling leading to a progressive increase in pulmonary vascular resistance; however, when this pathology is maintained, the afterload on the right ventricle is increased, and right ventricular hypertrophy occurs, ultimately resulting in right heart failure and death ( Mikhael et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%